2018
DOI: 10.19183/how.25.1.385
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Students’ Perceptions About English Learning in a Public University

Abstract: Explorando las percepciones de los estudiantes sobre el aprendizaje del inglés en una universidad pública* Patricia Kim Jiménez patricia.jimenez@uptc.edu.co Universidad Pedagógica y Tecnológica de Colombia, Tunja, ColombiaThis manuscript reports the final findings of an exploratory, descriptive case study that aimed at exploring the perceptions of a group of English as a foreign language students in a public university regarding their English learning and the commitment level through the process. A questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
0
10
0
7
Order By: Relevance
“…They reported that they felt difficulty in selecting appropriate learning strategy for developing listening skill. The informants' viewpoints reveals Jimenez's (2018) research finding where university students mostly felt difficult to get mastery over listening skill due to poor listening exposure.…”
Section: Strategies Employed In Listening Skillmentioning
confidence: 91%
See 2 more Smart Citations
“…They reported that they felt difficulty in selecting appropriate learning strategy for developing listening skill. The informants' viewpoints reveals Jimenez's (2018) research finding where university students mostly felt difficult to get mastery over listening skill due to poor listening exposure.…”
Section: Strategies Employed In Listening Skillmentioning
confidence: 91%
“…Simek (2006) argues that learning strategies are used to refer to all strategies that foreign language learners use in learning the target language, that is, they are the bases for any kinds of competence in foreign language. Jimenez's (2018) research reveals that learning strategies could also be used by bad language learners trying to become more successful in language learning. Language learning strategies enable the learners to achieve academic success if they are self regulated, self motivated and self directed.…”
Section: Benefits Of Learning Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A tenor de estos resultados se entiende que los alumnos universitarios estudian otros idiomas por necesidad, como cumplir con las exigencias de la Universidad (57.4%), frente a un 42.6% que lo hacen motu proprio, es decir, por razones particulares referidas al desarrollo académico y personal, conclusión que corroboran Gallardo et al (2010). No obstante, Jiménez (2018) halló que el 70% de los universitarios de su estudio aprendían inglés por motivos internos frente al 30% que lo hacía para cumplir con los requisitos universitarios. Por tanto, se plantea abordar en profunidad esta cuestión en futuras investigaciones.…”
Section: Discusión Y Conclusionesunclassified
“…Para el estudiantado dicha estrategia evaluativa les ha permitido reforzar lo aprendido en clase, además de explorar otros temas de manera independiente. Al respecto, se plantea que, si bien algunos estudios en el contexto de la política lingüística se han centrado en las percepciones del estudiantado en el contexto universitario (Kagwesage, 2012), sobre el reconocimiento del aprendizaje de idiomas en su formación profesional (Pereira, 2013) y el aprendizaje del inglés y su compromiso (Jiménez 2018), en esta investigación se traen las voces de un estudiantado que da cuenta de las fortalezas de la política lingüística y, muy en particular, su aceptación y reconocimiento frente a la evaluación del programa, la cual propende por una evaluación formativa, distanciándose de alguna manera de la evaluación tradicional que, por lo general, ha caracterizado los ambientes universitarios.…”
Section: Y Apropiación Interpretación Y Apropiación | Revista Virtualunclassified